Cyber Harassment of Public Figures: Causes and Importance of Legal Education - Ismail Dian Ekawaty; Puluhulawa Jufriyanto; Nggilu Novendri M.; Ahmad Ahmad; Siagian Ottow W.T.G.P. (E3S Web of Conferences)
This study explores the factors behind cyber harassment of public figures from the perspective of Indonesia’s Telematics Law and the importance of basic legal education for Indonesians. Methods include statutory, case, and conceptual approaches. Findings indicate that legal substance and culture contribute to cyber harassment. Legal substance refers to elements of the Electronic Information and Transactions Law, fulfilled if the content is public. However, cyber harassment often targets public figures privately. Regarding legal culture, many harassed public figures do not file complaints, viewing it as a job risk and feeling uncomfortable or threatened by reporting. Therefore, basic legal education is essential to improve legal awareness and understanding of rights and obligations.